2000
DOI: 10.1002/(sici)1097-4644(20000101)76:1<37::aid-jcb5>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Relative roles of T-cell receptor ligands and interleukin-2 in driving T-cell proliferation

Abstract: Stimulation of T cells by the T-cell receptor (TCR)/CD3 complex results in interleukin-2 (IL-2) synthesis and surface expression of the IL-2 receptor (IL-2R), which in turn drive T-cell proliferation. However, the significance of the requirement of IL-2 in driving T-cell proliferation, when TCR stimulation itself delivers potential mitogenic signals, is unclear. We show that blocking of IL-2 synthesis by Cyclosporin A (CsA) suppressed both the Concanavalin A (Con A)- and phorbol myristate acetate (PMA)/ionomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…Cytokines clearly play an important role in allowing survival and proliferation of activated T cells, and it has been shown that cytokine-mediated signals can control lymphocyte proliferation by regulating the expression of cell cycle proteins that control entry into the S phase of the cell cycle (22). We have shown that provision of at least IL-2 is necessary in our in vitro system, which is consistent with other studies demonstrating its importance in T cell proliferation (23)(24)(25). However, other cytokines such as IL-7 and/or IL-15, which have been recently implicated in regulating naive and memory T cell homeostasis (11)(12)(13)(14), may play important roles for in vivo T cell expansion following antigenic stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…Cytokines clearly play an important role in allowing survival and proliferation of activated T cells, and it has been shown that cytokine-mediated signals can control lymphocyte proliferation by regulating the expression of cell cycle proteins that control entry into the S phase of the cell cycle (22). We have shown that provision of at least IL-2 is necessary in our in vitro system, which is consistent with other studies demonstrating its importance in T cell proliferation (23)(24)(25). However, other cytokines such as IL-7 and/or IL-15, which have been recently implicated in regulating naive and memory T cell homeostasis (11)(12)(13)(14), may play important roles for in vivo T cell expansion following antigenic stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…Nef not only interferes with activation of p56 lck and as a consequence signaling via the IL-2R (52), but also hinders cell cycle progression by down-regulating cyclins D1 and A (53). Reduced production of IL-2 by CD4 ϩ T cells from the Tg mice may also have contributed to defective proliferation of these cells in vitro because T cells require IL-2 to complete the late portion of the G 1 phase and enter the S phase of the cell cycle (54). Proliferative responses to mitogens (55), C. albicans Ags (56), and stimulation with anti-CD3 (57) are all impaired in patients infected with HIV, accompanied by impaired induction of the early activation marker CD69 (57) and diminished IL-2 production (58).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not examined NFAT activation in DKO T cells, our finding of normal IL-2 production suggests that any potential decrease in NFAT activation does not affect IL-2 secretion by these cells. Interaction of IL-2 with its high-affinity receptor induces further up-regulation of CD25 and delivers critical proliferation signals (24). WT and WASP KO T cells that had been first activated with OVAp then washed and stimulated with exogenous IL-2 further up-regulated CD25 expression (Fig.…”
Section: Dko T Cells Express Il-2 Receptor (Il-2r) and Secrete Il-2 Nmentioning
confidence: 98%